2004
DOI: 10.1124/jpet.104.076950
|View full text |Cite
|
Sign up to set email alerts
|

Ciglitazone-Induced Lenticular Opacities in Rats: In Vivo and Whole Lens Explant Culture Evaluation

Abstract: The cataractogenic potential of the thiazolidinedione ciglitazone (CIG) was investigated in vivo and in vitro. In the rat, CIG caused a dose-dependent (30 -300 mg/kg/day) increase in incidence and severity of nuclear cataract formation during a 3-month nonclinical safety assessment study. Potential mechanisms of toxicity were surveyed using whole rat lens explants exposed to CIG with or without various inhibitors of cataract formation. In vitro, CIG caused a concentration-(0.375-30 M) and time-dependent (3-24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Adult Sprague-Dawley rats were euthanized by CO 2 asphyxiation followed by exsanguination, and their eyes were enucleated and stored at 4 °C in Belzer UW cold preservation media (Bridge to Life), supplemented with 100 μg/mL penicillin (Invitrogen), 100 μg/mL streptomycin (Invitrogen), and 200 μg/mL d-glutamine (Invitrogen) following published protocols [26, 27]. Lenses were then carefully dissected from the globes and incubated in 4 mL Media 199 (Invitrogen) supplemented with 1% w/v of penicillin (100 μg/mL) and streptomycin (100 μg/mL) pre-incubated in 5% CO 2 atmosphere at 37 °C for 24 h. Non-cloudy lenses were either exposed to 10 min of UV light (365 nm, 12 mW/cm 2 ) or left unirradiated.…”
Section: Methodsmentioning
confidence: 99%
“…Adult Sprague-Dawley rats were euthanized by CO 2 asphyxiation followed by exsanguination, and their eyes were enucleated and stored at 4 °C in Belzer UW cold preservation media (Bridge to Life), supplemented with 100 μg/mL penicillin (Invitrogen), 100 μg/mL streptomycin (Invitrogen), and 200 μg/mL d-glutamine (Invitrogen) following published protocols [26, 27]. Lenses were then carefully dissected from the globes and incubated in 4 mL Media 199 (Invitrogen) supplemented with 1% w/v of penicillin (100 μg/mL) and streptomycin (100 μg/mL) pre-incubated in 5% CO 2 atmosphere at 37 °C for 24 h. Non-cloudy lenses were either exposed to 10 min of UV light (365 nm, 12 mW/cm 2 ) or left unirradiated.…”
Section: Methodsmentioning
confidence: 99%
“…In the lens, mitochondrial Ca 2þ signalling has not been specifically investigated. However, interestingly and contrary to what might be anticipated, the blocker of the Ca 2þ uniporter, ruthenium red, inhibited lens opacification in organ cultured rat lenses exposed to the cataractogenic compound ciglitazone (Aleo et al, 2005). The role of mitochondria in modulating Ca 2þ dynamics in lens cells, particularly in relation to cataractogenesis, certainly warrants further investigation.…”
Section: The Mitochondrial Uniportermentioning
confidence: 84%
“…They suggest that ATP depletion, in combination with an apoptotic stimulus, initiates a switch from apoptosis to necrosis. Recently, a concentration-and time-dependent ATP depletion after ciglitazone treatment was found in explanted Sprague-Dawley rat lenses (Aleo et al, 2005), whereas we observed ATP depletion in Jurkat P Ϫ cells. In line with reports in rat hepatocytes (Haskins et al, 2001), troglitazone and the combination of rotenone/TTFA did not significantly reduce the ATP content.…”
Section: Discussionmentioning
confidence: 51%